Analisis Pengendalian Persediaan Bahan Baku Dengan Metode Material Requirement Planning Pada Toko Roti Rejeki di Mijen, Semarang - Rizky Candra Ramadhan; Sunarso Sunarso (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the efficiency of raw material inventory control for bread products at Rejeki Bakery in Mijen, Semarang, and to examine the application of the Material Requirement Planning (MRP) method in optimizing raw material inventory costs. The research employs a quantitative approach using secondary data as the main source. The data analysis technique utilized in this study is the Material Requirement Planning (MRP) method, which includes three inventory control techniques: Lot For Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ). Each method was analyzed to determine the most efficient inventory cost. The results show that the raw material inventory cost using the Lot For Lot (LFL) method is Rp 2,400,000.00, the Economic Order Quantity (EOQ) method results in an inventory cost of Rp 2,992,600.00, while the Period Order Quantity (POQ) method incurs a cost of Rp 6,924,800.00. Additionally, the current raw material inventory cost under Rejeki Bakery’s management policy is Rp 2,681,600.00. Based on these findings, the implementation of the Material Requirement Planning (MRP) method at Rejeki Bakery in Mijen, Semarang, has demonstrated its effectiveness in improving the efficiency of inventory management. Among the three techniques analyzed, the Lot For Lot (LFL) method proves to be the most cost-effective, as it minimizes excess inventory while ensuring that production needs are met. This study highlights the importance of selecting an appropriate inventory control method to optimize costs and enhance operational efficiency in bakery production.